The Importance of the Halal Supply Chain During Covid-19 Pandemic - Rina Qurniawati; Yulfan Nurohman; Adjil Izzii (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2022)
The purpose of this study is to examine the relationship between halal supply chain awareness toward attitude and purchase intention. A questionnaire was designed to collect data from Islamic undergraduate students in Salatiga and Surakarta. Partial Least Square (PLS) software was used to test the proposed research model. This research becomes the first research on how specific halal supply chain awareness affects the consumer during pandemic Covid-19. The result shows that halal feed and halal slaughtering have a positive effect on attitude. Proper separation and attitude significantly influence purchase intention, meanwhile, the halal feed and halal slaughtering awareness insignificantly influence purchase intention.